Graphene/Cu Nanoparticle Hybrids Fabricated by Chemical Vapor Deposition As Surface-Enhanced Raman Scattering Substrate for Label-Free Detection of Adenosine - Xu, Shicai; Man, Baoyuan; Jiang, Shouzhen; Wang, Jihua; Wei, Jie; Xu, Shida; Liu, Hanping; Gao, Shoubao; Liu, Huilan; Li, Zhenhua; Li, Hongsheng; Qiu, Hengwei (ACS applied materials & interfaces, 2015)
We present a graphene/Cu nanoparticle hybrids (G/CuNPs) system as a surface-enhanced Raman scattering (SERS) substrate for adenosine detection. The Cu nanoparticles wrapped by a monolayer graphene shell were directly synthesized on flat quartz by chemical vapor deposition in a mixture of methane and hydrogen. The G/CuNPs showed an excellent SERS enhancement activity for adenosine. The minimum detected concentration of the adenosine in serum was demonstrated as low as 5 nM, and the calibration curve showed a good linear response from 5 to 500 nM. The capability of SERS detection of adenosine in real normal human urine samples based on G/CuNPs was also investigated and the characteristic peaks of adenosine were still recognizable. The reproducible and the ultrasensitive enhanced Raman signals could be due to the presence of an ultrathin graphene layer. The graphene shell was able to enrich and fix the adenosine molecules, which could also efficiently maintain chemical and optical stability of G/CuNPs. Based on the G/CuNPs system, the ultrasensitive SERS detection of adenosine in varied matrices was expected for the practical applications in medicine and biotechnology.